Determination Of Mannings Coefficient For Modular Channel - Dinail, Nurul Juliyana (Universiti Sains Malaysia, 2017)
A subsurface modular channel is a part of an environmental friendly dual drainage system comprises of grassed swale on top and a conveyance conduit beneath it. Bio – ecological Drainage System (BIOECODS) has implemented this concept for ecological swales that were built around Engineering Campus, Universiti Sains Malaysia. Constant researches and developments have been carried out by River Engineering and Urban Drainage Research Centre (REDAC) to improve the application of BIOECODS. Laboratory tests on a newly – designed as well as pre – existing module were carried out to determine its Manning’s coefficient and to study the behaviour of the flow for each module through the flow rating curves. 21 sets of experiments were done based on different flow depths and slope conditions. The modules were tested under three different slopes; 1:500, 1:750 and 1:1000 with flow depths varying from 10 – 40 cm. Both of the modules labelled as Module 1 (existing design) and Module 2 (new design) had shown differences in terms of flow and Manning’s n. A comparison has also been made between Module 2 which was a triple arrangement module with previous study that used the same type of module but only had a single arrangement. The newly – designed module was observed to have better flow than Module 1. Manning’s n determined from this study will be used for future design and further study. This research is important for efficiency evaluation of a modular channel to act in subsurface drainage system thus to help in solving surface water runoff problems especially during peak flow.